Scalable photonic-phonoinc integrated circuitry for reconfigurable signal processing - Liang Zhang; Chaohan Cui; Yongzhou Xue; Paokang Chen; Linran Fan (Nature Communications)
Abstract The interaction between photons and phonons plays a crucial role in broad areas ranging from optical sources and modulators to quantum transduction and metrology. The performance can be further improved using integrated photonic-phononic devices, promising enhanced interaction strength and large-scale integration. While the enhanced interaction has been widely demonstrated, it is challenging to realize large-scale integrated photonic-phononic circuits due to material limitations. Here, we resolve this critical issue by using gallium nitride on sapphire for scalable photonic-phononic integrated circuits. Both optical and acoustic fields are confined in sub-wavelength scales without suspended structures. This enables us to achieve the efficient launching, flexible routing, and reconfigruable processing of optical and acoustic fields simultaneously. With the controlled photonic-phononic interaction and strong piezoelectric effect, we further demonstrate the reconfigurable conversion between frequency-multiplexed RF and optical signals mediated by acoustics. This work provides an ideal platform for achieving ultimate performance of photonic-phononic hybrid systems with high efficiency, multiple functions, and large scalability.